Assessment of polycyclic aromatic hydrocarbon pollution in the sludge and soil of the Dnistrova canyon within the boundaries of the Horodenkiv territorial community - BEREZOVSKIY, Oleksii; MIDYK, Svitlana; KORNIYENKO, Valentina; SAMKOVA, Oksana; TONKHA, Oksana; VISHOVAN, Yurii; SEMENKO, Larysa; SMYRNYY, Maksym (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. An assessment of the state of pollution by ecotoxicants of soils and river sediments in the territory of the Horodenkiv territorial community, adjacent to the Dniester Regional Landscape Park (RLP) and located on the right bank of the Dniester River, was carried out. Methods. High-performance liquid chromatography (HPLC) was used to analyze samples of silt and soil for the content of 15 polycyclic aromatic hydrocarbons (PAHs): naphthalene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benz(a)anthracene, chrysene, benz(b)fluoranthene, benz(k)fluoranthene, benz(a)pyrene, dibenz(a,h)anthracene, benz(g,h,i)perylene, indeno(1,2,3-cd)pyrene. Sampling was carried out in locations in Kolomyia district, Ivano-Frankivsk region, which are remote from pollution sources (background content of pollutants) and directly near pollution sources (highways, wastewater). Results. Among all the selected samples of surface soil and river sediment, the sum of the concentration of 15 PAHs was the lowest in forest soil (103 μg/kg). In the sample of river sediment of the Dniester River, the total concentration was 449 μg/kg. In the samples of river sediment of the Lemyts and Derenovets rivers, in the direction from the settlements of the village of Strilche and the village of Serafyntsi to the Dniester, the total concentration of PAHs was significantly higher than in the Dniester River. It decreased in this direction from the maximum of 11471 μg/kg (samples taken to treatment facilities) to 2005 μg/kg. On the banks of the Lemyts River it was 583 μg/kg in the soil. Conclusions. The high concentration of PAHs in individual samples of river sediment of the Lemyts River and the Derenovets River may be due to their proximity to roads and settlements, their active accumulation due to the slow biodegradation of these compounds in the river sediment. The highest concentration of the total PAHs (64.034 mg/kg) was found in the soil on the side of the regional road P24. In soil samples taken at a distance of 300 m from this road, a small content of all 15 PAHs (275 μg/kg) with a benzo(a)pyrene concentration of 9.29 μg/kg was found, which are lower values than the maximum permissible concentration (20 μg/kg). The dominance of 4–5-ring surfactants (fluoranthene, pyrene, chrysene, benz(a)anthracene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene) indicates the long-term impact of pollution sources and the accumulation of these substances in the soil.